1982
DOI: 10.1097/00132586-198202000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Atropine and Glycopyrrolate on Various End-Organs

Abstract: Summary: Atropine and glycopyrrolate (glycopyrronium bromide), a quaternary ammonium drug, were evaluated in volunteers following intramuscular administration with respect to effects on various end-organs with cholinergic innervation. Glycopyrrolate appears to be five to six times more potent than atropine in its antisialogogue effect and also exhibits a selective, though prolonged, effect on salivary secretion and sweat gland activity. It has minimal cardiovascular, ocular and central nervous system effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 11 publications
1
24
1
1
Order By: Relevance
“…The use of glycopyrronium was generally preferred as second line. Further consideration could be given to this treatment as a first line option, especially given its relatively low rates of adverse effects, in part due to its poor penetration of the blood brain barrier [25].…”
Section: Discussionmentioning
confidence: 99%
“…The use of glycopyrronium was generally preferred as second line. Further consideration could be given to this treatment as a first line option, especially given its relatively low rates of adverse effects, in part due to its poor penetration of the blood brain barrier [25].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] The dose of glycopyrrolate given in phase II of our study (0.2 mg) was therefore not quite equipotent to the hyoscine given in phase I. A review of the literature on the antisialogogue effects of antimuscarinics showed that glycopyrrolate has a slower onset of antisialogogue action than hyoscine HBr in the normal dose ranges.…”
Section: Discussionmentioning
confidence: 67%
“…If bradycardia occurs because too much dexmedetomidine has been administered too quickly it can be treated readily with atropine. Atropine is preferred to glycopyrrolate for serious bradycardia because it has stronger effect on cardiac muscarinic receptors [58]. Ephedrine and epinephrine can also be used to treat bradycardia if hypotension is present.…”
Section: Funding Sourcesmentioning
confidence: 99%